The Relationship between the North Atlantic Jet and Tropical Convection over the Indian and Western Pacific Oceans - Yuan, Jiacan; Feldstein, Steven B.; Lee, Sukyoung; Tan, Benkui (Journal of Climate, 2011)
Boreal winter jet variability over the North Atlantic is investigated using 40-yr European Centre for Medium-Range Weather Forecasts Re-Analysis (ERA-40) data, where the variability is defined by the first EOF of the zonal wind on seven vertical levels. The principal component time series of this EOF is referred to as the jet index. A pattern correlation analysis indicates that the jet index more accurately describes intraseasonal North Atlantic zonal wind variability than does the North Atlantic Oscillation (NAG). A series of composite calculations of the jet index based on events of intraseasonal convective precipitation over the tropical Indian and western Pacific Oceans reveals the following statistically significant relationships: 1) negative jet events lead enhanced Indian Ocean precipitation, 2) positive jet events lag enhanced Indian Ocean precipitation, 3) positive jet events lead enhanced western Pacific Ocean precipitation, and 4) negative jet events lag enhanced western Pacific Ocean precipitation. These intraseasonal relationships are found to be linked through the circumglobal teleconnection pattern (CTP). Implications of the sign of the CTP being opposite to that of the jet index suggest that relationships 1 and 3 may arise from cold air surges associated with the CTP over these oceans. On interdecadal time scales, a much greater increase in the frequency of precipitation events from 1958 to 1979 (P1)10 1980 to 2001 (P2) was found for the Indian Ocean relative to the western Pacific Ocean. This observation, combined with relationships 2 and 4, leads to the suggestion that this change in the frequency of intraseasonal Indian Ocean precipitation events may make an important contribution to the excitation of interdecadal variability of the North Atlantic jet. Meteorology & Atmospheric Sciences SCI(E) EI 4 ARTICLE 23 6100-6113 24